Assessing Students’ Physics-Science Literacy Skills on Impulse and Momentum Through Real-Life Activities - Arifah, Laila Rahma; Satriawan, Muhammad; Jatmiko, Budi; Prahani, Binar Kurnia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This research aims to analyze students' science literacy on the topic of impulse and momentum based on the Program for International Student Assessment (PISA) competencies. This study uses a descriptive approach involving 22 high school students. The instrument used consisted of three essay questions (constructed-response) developed based on real-world contexts and aligned with PISA science literacy indicators. Students' answers are assessed using a PISA-based scoring rubric to categorize the level of science literacy achievement. The research results show that students' science literacy achievements vary across each competency. The competence to explain phenomena scientifically and design and evaluate scientific investigations falls into the Fair category, while the competence to interpret scientific data and evidence scientifically falls into the Poor category. These findings indicate that students are relatively capable of recognizing and explaining physical phenomena and have a preliminary understanding of scientific investigations, but still struggle with interpreting data and accurately relating it to physical concepts. The implication of this research is the need to strengthen learning strategies that emphasize data interpretation skills, such as thru the analysis of experimental results, graphs, and context-based reasoning questions. Inquiry-based and problem-based learning approaches are recommended to support the more comprehensive development of science literacy. This study has limitations in the small sample size, the limited number of instruments, and the research context being conducted in only one school. Subsequent research is recommended to involve a larger sample and more diverse instruments.